Attuning to religious and cultural pluralism: criminal and civil perspectives - Sona, Federica (Il diritto ecclesiastico, 2022)
In the xxi century, legislative and judicial bodies are required to overcome the difficulties embedded in attuning to an evolving melange of coexisting differences and pluralities. Building upon Italian landmark judicial decisions, the paper explores criminal and civil perspectives on culture and religion when identity-components come into play. The analysis concentrates on the parents’ right to ensure cultural and religious education to their offspring as counterbalanced by the children’s right to health and bodily integrity. The balancing exercise undertaken by the judiciary between the offspring’s right to co-parenting and the limit posed to the reunification of transnational family members on European soil is also investigated. Challenged by multiculturalism, interlegality and inter-normativity, the efforts made by Italian courts and tribunals are to be praised. Whereas the outcome of some decisions might be disputable, the trajectory outlined by the judiciary in coping with the contemporary super-diverse society is not a straight line ; grey areas do exist where room for manoeuvre can be found. Accordingly, while calling for a profound reassessment and theoretical regrounding of legal categories in light of diverse value taxonomies and multiple identity markers, the essay shows that a fresh vocabulary of coexistence is being gradually agreed upon and cautiously developed.